2021
DOI: 10.1111/jrh.12597
|View full text |Cite
|
Sign up to set email alerts
|

Rural disparities in end‐of‐life care for patients with heart failure: Are they due to geography or socioeconomic disparity?

Abstract: Purpose The impact of rurality and socioeconomic deprivation on end‐of‐life (EOL) care for patients with heart failure (HF) is unknown. We analyzed claims to describe the prevalence and predictors of EOL health care utilization for patients dying with HF in a predominantly rural state. Methods We used the MaineHealth Data Organization's All‐Payer Claims Data to identify 15,168 patients ≥35 who died with HF between 2012 and 2017. The primary outcome was health care utilization during the last 180 days of life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(100 reference statements)
0
7
1
Order By: Relevance
“…Access to health care is a societal driver of rural-urban disparities and is singled out as a top priority in the Rural Healthy People 2020 report . Differing access to care in rural areas can negatively influence health outcomes; specifically within HF after diagnosis, rural patients have a longer delay in care and reduced emergency department visits, hospitalizations, and hospice use . In addition to affecting outcomes, access to care can affect disease incidence because of inequities in levels of preventive care and risk factor management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to health care is a societal driver of rural-urban disparities and is singled out as a top priority in the Rural Healthy People 2020 report . Differing access to care in rural areas can negatively influence health outcomes; specifically within HF after diagnosis, rural patients have a longer delay in care and reduced emergency department visits, hospitalizations, and hospice use . In addition to affecting outcomes, access to care can affect disease incidence because of inequities in levels of preventive care and risk factor management.…”
Section: Discussionmentioning
confidence: 99%
“…32 Differing access to care in rural areas can negatively influence health outcomes; specifically within HF after diagnosis, rural patients have a longer delay in care and reduced emergency department visits, hospitalizations, and hospice use. 10,33,34 In addition to affecting outcomes, access to care can affect disease incidence because of inequities in levels of preventive care and risk factor management. Future research should examine the impact of preventive care utilization on risk of HF and chronic disease among rural residents.…”
Section: Rurality and Hfmentioning
confidence: 99%
“…Studies have found rural patients were less likely to receive hospice care than urban patients. 8,19,20 Racial disparity in hospice use persists regardless of geographic residence. For example, a study on lung cancer patients' use of hospice care reported that African-Americans were 21% less likely to use hospice care than Whites in both rural and urban areas.…”
Section: Disparity Of Hospice Awareness and Hospice Use Among African...mentioning
confidence: 99%
“…In addition to racialized populations receiving poorer end‐of‐life care, other social determinants of health also contribute to inequities. Individuals with limited access to health care due to geographic location, and those with lower socioeconomic status are also known to receive inequitable end‐of‐life care (Hutchinson et al, 2021; Noh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Though some studies have been conducted on health inequities in end‐of‐life care and how to promote health equity by addressing social determinants of health (Bazargan & Bazargan‐Hejazi, 2021; Brown et al, 2018; Hutchinson et al, 2021; Noh et al, 2021), progress is hampered by complex and multi‐faceted nature of both end‐of‐life care and social determinants of health (Alvidrez et al, 2019). End‐of‐life care requires holistic and individualized approaches in response to physical, psychological, social and spiritual needs through a multidisciplinary team (Finucane et al, 2021; Nelson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%